1993
DOI: 10.1093/genetics/135.4.955
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a single-copy tRNA affects microtubule function in Saccharomyces cerevisiae.

Abstract: rts1-1 was identified as an extragenic suppressor of tub2-104, a cold-sensitive allele of the sole gene encoding beta-tubulin in the yeast, Saccharomyces cerevisiae. In addition, rts1-1 cells are heat sensitive and resistant to the microtubule-destabilizing drug, benomyl. The rts1-1 mutation is a deletion of approximately 5 kb of genomic DNA on chromosome X that includes one open reading frame and three tRNA genes. Dissection of this region shows that heat sensitivity is due to deletion of the open reading fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A third isoacceptor is tRNA Arg1 CCU , which reads the AGG codon. It is encoded by a single gene copy and is dispensable, as shown by the viable phenotype of the knockout strain (23). Indeed, AGG codons can be read by tRNA Arg2 ICG .…”
Section: Discussionmentioning
confidence: 99%
“…A third isoacceptor is tRNA Arg1 CCU , which reads the AGG codon. It is encoded by a single gene copy and is dispensable, as shown by the viable phenotype of the knockout strain (23). Indeed, AGG codons can be read by tRNA Arg2 ICG .…”
Section: Discussionmentioning
confidence: 99%
“…This gene rts1 was identified as an extragenic suppressor of tub2-104. Tub2-104 is a cold-sensitive allele of the gene encoding βtubulin in S. cerevisiae (Reijo et al 1993). Individual growth validation of the homozygous diploid strain that lacks this gene showed that this strain had only 33% growth (67% inhibition) in the presence of 10 µM of PelA after 20 generations ( Fiedler et al 2009).…”
Section: Pela Hop Microarray Hitsmentioning
confidence: 99%